IMPLEMENTASI METODE SAW PADA SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMILIH ANGGOTA UKM CATUR UGM UNTUK DIKIRIM KE AJANG PERTANDINGAN - , ANDRI SETIANINGSIH; , Adhistya Erna Permanasari, S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Gadjah Mada University is one university that has a Student Activity Unit the largest in Indonesia. One active sport unit is chess unit, where one of the main agenda is to follow chess championships in university, regional, or national level. Because the funds is not possible to finance all members to participate in the championship, so should held the selections to get the right and deserve player to sent in the championship. The selection only with the home tournament is less effective because it still has some flaw, it so can made some problems. Fuzzy Multiple Attribute Decision Making (FMADM) is one method of decision support system for selecting the best alternative from a number of alternatives based on criteria. One method in FMADM is Simple Additive Weighting (SAW). SAW method is based on the concept of ranking with the pair comparison between alternatives on criteria. The purpose of this research is to apply the SAW method in the decision making in chess player selection. The results showed that the selection process is influenced by the criteria and an alternative interest rate comparisons among criteria. The criteria used are the result of selection, discipline, performance of the last 3 months, 1 year recent achievements, and titles. The results of this research is the system can provide a list rangking of alternative based on value preferences. Greatest preference value indicates the feasible and reasonable alternatives to be sent to the tournamnent.